Molecular discrimination of Echinococcus granulosus and Echinococcus multilocularis by sequencing and a new PCR-RFLP method with the potential use for other Echinococcus species - Sakalar, Cagri; Kuk, Salih; Erensoy, Ahmet; Dagli, Adile Ferda; Ozercan, Ibrahim Hanifi; Cetinkaya, Ulfet; Yazar, Suleyman (Tubitak Scientific & Technological Research Council Turkey, 2014)
Background/aim: To develop a novel polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) protocol using a new genomic marker sequence and a novel set of restriction enzymes in order to detect and discriminate 2 Echinococcus species, E. granulosus and E. multilocularis, found in formalin-fixed paraffin-embedded (FFPE) human tissues. Materials and methods: DNA was isolated from 11 FFPE human tissue samples positive for cystic echinococcosis or alveolar echinococcosis. A mitochondrial genomic marker region was amplified and sequenced using a novel primer pair and a new PCR-RFLP protocol was developed for the detection and discrimination of E. granulosus and E. multilocularis using a set of restriction enzymes including AccI, MboI, MboII, and TsoI. Results: The selected marker region was amplified using DNA isolated from FFPE human tissue samples positive for cystic echinococcosis or alveolar echinococcosis and the discrimination of E. granulosus and E. multilocularis was accomplished by use of the novel PCR-RFLP method. Conclusion: In this PCR-RFLP protocol, use of any single restriction enzyme is enough for the discrimination of E. granulosus and E. multilocularis. The PCR-RFLP protocol can be potentially used for the discrimination of 5 other Echinococcus species: E. oligarthus, E. shiquicus, E. ortleppi, E. canadensis, and E. vogeli.
Keywords: FFPE tissues; Echinococcus granulosus; Echinococcus multilocularis; sequencing; PCR-RFLP